2014
DOI: 10.1111/asj.12207
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of energy metabolism and meat quality among three pig breeds

Abstract: The objective of this study was to evaluate the effects of muscle-fibre types and hormones on glycolytic potential and meat quality traits and their association with glycolytic-related gene expression in three different altitude pig breeds. The pig breeds studied were the Tibetan pig (TP, high altitude), the Liang-Shan pig (LSP, middle altitude) and the Duroc×(Landrace×Yorkshire) cross (DLY, flatland). The results indicated that TP and LSP had better meat quality than DLY (P<0.01). The glycolytic potential (GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
56
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 36 publications
10
56
1
1
Order By: Relevance
“…In the present study, we have compared meat quality traits in the Rongchang with the Landrace at 161 days of age. Consistent with previous results on different genotype pigs (Miao et al, 2009;Guo et al, 2011;Shen et al, 2014), our results showed that Rongchang pigs exhibited better meat quality compared with the Landrace at the same age.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, we have compared meat quality traits in the Rongchang with the Landrace at 161 days of age. Consistent with previous results on different genotype pigs (Miao et al, 2009;Guo et al, 2011;Shen et al, 2014), our results showed that Rongchang pigs exhibited better meat quality compared with the Landrace at the same age.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the Jinhua pigs (Miao et al, 2009;Guo et al, 2011) and Laiwu pigs (Hu et al, 2008) exhibited better meat quality traits when compared with the Landrace and Duroc pigs, respectively. Moreover, Ruusunen et al (2012) and Shen et al (2014) also found differences in meat quality traits between different genotype pigs. In the present study, we have compared meat quality traits in the Rongchang with the Landrace at 161 days of age.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although it is well known that different pig breeds differ in carcass and meat quality traits (Ruusunen et al, 2012;Shen et al, 2014) the molecular mechanisms underlying these differences remain unclear. Usually, differences in meat quality traits are smaller between commercial pig breeds, because the goals of pig breeding, such as fast growth and leanness of the carcass have been similar for a long time (Ruusunen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%